(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Giurisprudenza e dottrina prima della sentenza - 2. La sentenza: l’insegnamento di religione cattolica e la laicità - 3. Benefici e costi del “nuovo” principio supremo - 4. La quiete dopo la sentenza - 5. Lo “sgonfiamento” del principio supremo - 6. La recezione della laicità. Thirty years of Secularism (rereading Italian Constitutional Court 1989/203 and the subsequent Constitutional Jurisprudence) ABSTRACT: The paper rereads at a distance of thirty years the italian leading case about the secularism and findes its underutilization as highest principle, in favour of the “ordinary” principles of equality and freedom of religion, and its not large, at times unnamed, reception in the jurisprudence.